Cooperation of teachers and parents in forming discipline characters of students of sman 1 lembah gumanti - Elfina Camelisa; Firman Firman; Rusdinal Rusdinal (Indonesian Institute For Counseling, Education and Therapy, 2020)
The purpose of this study was to describe how schools should shape social care characteristics for students of SMAN 1 Lembah Gumanti. This research is motivated by a lack of understanding of the importance of subjects in students and parents, so that a cooperative relationship between parents and teachers is needed to shape student subjects. This type of research used data collection techniques in descriptive and qualitative forms such as observation, interviews, and literature study. This study describes and shows the fact that teachers have worked hard to work with parents, including: fostering a good relationship between parents and teachers, providing direction and learning about character education, including parents in this character education program, then also creating a mutual agreement between teachers and parents regarding the limits on the use of devices and social media for students. Coordinating teacher visits to students' homes to further monitor the policies that have been made. With the active role of both parties between teachers and parents, it is hoped that they will be able to realize the character building program for students.